Psychoneuroendocrinological effects of music therapy versus mindfulness in palliative care: results from the ‘Song of Life’ randomized controlled trial - Köhler, Friederike; Keßler, Jens; Stoffel, Martin; Weber, Martin; Bardenheuer, Hubert J.; Ditzen, Beate; Warth, Marco (Supportive care in cancer, 2022)
Purpose  Although research on psychosocial interventions in palliative care provided evidence for their effectiveness regarding patient-reported outcomes, few studies have examined their psychobiological effects yet. Therefore, the purpose of the present work as part of an overarching study was to investigate differential effects of music therapy versus mindfulness on subjective distress and both neuroendocrine and autonomic stress biomarkers. - Methods  A total of 104 patients from two palliative care units were randomly assigned to three sessions of either music therapy or mindfulness. Before and after the second session (completed by 89 patients), participants rated their momentary distress and provided three saliva samples for cortisol and α-amylase analysis. Furthermore, photoplethysmography recordings were continuously assessed to calculate mean heart rate and heart rate variability. Data were analyzed using multilevel modeling of all available data and sensitivity analysis with multiply imputed data. - Results  Between 67 and 75% of the maximally available data points were included in the primary analyses of psychobiological outcomes. Results showed a significant time*treatment effect on distress (b =  − 0.83, p = .02) indicating a greater reduction in the music therapy group. No interaction effects were found in psychobiological outcomes (all p > .05), but multilevel models revealed a significant reduction in cortisol (b =  − 0.06, p = .01) and mean heart rate (b =  − 7.89, p = .05) over time following either intervention. - Conclusion  Findings suggest a beneficial effect music therapy on distress while no differential psychobiological treatment effects were found. Future studies should continue to investigate optimal stress biomarkers for psychosocial palliative care research.
Published online: 6 August 2021
Gesehen am 12.06.2023